Structural Characteristics of Placenta Tissue after Incubation with DMSO - Govorukha, T. P.; Repin, N. V.; Tsupikov, O. M. (Problems of Cryobiology and Cryomedicine, 2006)
Structural characteristics of placenta tissue after incubation with DMSO were studied. After incubating the placenta fragments with 8% DMSO the most manifested ultrastructural changes were shown to be revealed in a surface layer of chorion villi, that was syncitiotrophoblast.